Earning Per Share, Debt To Equity Ratio dan Price Earning Ratio terhadap Harga Saham pada Perusahaan Farmasi di BEI - Salaste, Ibel; Nurlaela, Siti; Suhendro (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2021)
The development of the health world will certainly have a positive impact for shareholders especially in pharmaceutical companies, this is reflected by the Government's support thatprovides ease and incentives in the form of tax deductions and import duties borne by theGovernment to attract investments. With these opportunities will certainly affect the price ofstocks in pharmaceutical companies including the financial performance. Financial performance can be seen from several financial ratios, earning per share, debt to equity, andprice earning ratio. Samples on this study were as many as 7 companies for 5 years so in 35 can sample. The results of this study simultaneously all variables in this study have an effect on the stock price. Both EPS and PER variables affect the stock price, while the DER variablesnegatively affect the share price.